The impact of gas reserves recovery on the technological and economic performance of gas condensate field minig - Fyk, Illia; Kryvulia, Serhii; Sinkevych, Iryna; Fyk, Illia (IOP Publishing, 2024)
One of the key challenges of modern times is ensuring effective access to resources for the population, industry, and economic needs. Natural gas plays a crucial role as a primary energy and industrial resource. Achieving energy and economic independence for Ukraine largely depends on the ability to meet the needs of industry and the population with domestic natural gas. Given the limited resource base, the lack of new fields, and the depletion of existing ones, the effective development of current gas condensate fields becomes particularly important. This study examines the possibilities of reserves recovery using one of the largest gas condensate fields in Ukraine - the Shebelinka field - as an example. The author has demonstrated the occurrence of reserves recovery at this field. In this work, the author has developed forecast ща the impact of reserves recovery on the technological and economic performance of gas condensate field development.
Keywords: gas reserves; gas; gas condensate; gas condensate minig; gas condensate field; natural gas